Study on Temperature Field Characteristic of Surface Modified Gear based on Phosphating Coating - Jia Sen; Chen Yong; Zang Libin; Wu Yimin (Jixie chuandong)
In order to study the effect of manganese phosphate conversion coating on gear meshing temperature,based on gear meshing theory,tribology theory and heat transfer theory,combined with the friction coefficient according to the SRV friction wear tests with coating and non-coating,the friction heat flux density and the convective heat transfer coefficient and load of the gears are calculated accurately. Finally,the steady-state temperature distribution of the gear teeth before and after coating is obtained,and the influence of the speed and torque on the steady temperature field of the gears is analyzed. The results show that the maximum temperature of the gears after coating treatment is lower than that of the uncoated gears,which provides a reference for the study of fatigue resistance and scuffing resistance of gears.